SISTEM INFORMASI PENJUALAN SPARE PART SEPEDA BMX BERBASIS WEBSITE DI TOKO MS CYCLES - Roni Rizki Parlindungan (Shofanah Media Berkah, 2023)
The development of the world of technology and information is getting faster day by day. These developments clearly affect the speed and accuracy of information delivery. Unfortunately, there are still many business activities, especially the buying and selling process, which are not in line with current technological advances. On that basis, the author tries to make a final project regarding the sales system at the Bicycle Shop, which currently sales management is still manual. Most systems that run at the Bicycle Shop are done manually, starting from recording products, selling goods, and making reports so that it is possible during the process there is an error in recording. The design of this sales information system is the best solution to overcome the problems that occur in the Bicycle Shop. For the software development method, the author uses the Prototype model. In making this sales information system using a programming language using PHP and using a MySQL database. This sales information system provides information on some common processes that often occur in bicycle shops. The expected results from making this sales information system able to provide information quickly and accurately are expected with this information system, users can increase profits in their business.